211k views
3 votes
Choose the equation that represents the asymptote of the graph f(x) - 2^x + 3 y = 0y = 3x=0x=3

User Leniaal
by
5.1k points

1 Answer

2 votes

Given the function :


y=2^x+3

The given function is exponential function

the graph of the function is as shown in the following image:

So, the equation that represents the asymptote of the graph is:


y=3

Choose the equation that represents the asymptote of the graph f(x) - 2^x + 3 y = 0y-example-1
User Top Cat
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.